2018
DOI: 10.1111/jocn.14631
|View full text |Cite
|
Sign up to set email alerts
|

The educational needs of nursing staff when working with hospitalised older people

Abstract: There was an incongruence between survey and interview data as nursing staff reported gaps in their knowledge despite moderately high scores on the Knowledge about Older People Quiz. Further research is needed to understand additional factors that influence nurses' educational needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Learning activity 2 will focus on cognitive impairment (delirium, dementia, and depression), including positive modelling on how to manage anxiety and aggression in older people with these conditions. Previous research identified that student and practicing nurses do not feel equipped to work with older people with dementia [ 28 , 43 , 64 , 65 ]. We estimate participants will take 3 h to complete this activity.…”
Section: Methodsmentioning
confidence: 99%
“…Learning activity 2 will focus on cognitive impairment (delirium, dementia, and depression), including positive modelling on how to manage anxiety and aggression in older people with these conditions. Previous research identified that student and practicing nurses do not feel equipped to work with older people with dementia [ 28 , 43 , 64 , 65 ]. We estimate participants will take 3 h to complete this activity.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes, older patients desire to be model patients and choose not to bother the nursing staff (33), and when these patients suffer multiple illnesses, they may become passive (34). Despite challenges in caring for older cancer patients (10), knowledge about the individual life values of these patients can help with communication (35).…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration and clear communication with patients and family members are also emphasised (9). Caring for hospitalised older patients is complex (10) because of the heterogeneity of the population. Patient self-management in older patients can range from good physical and mental functioning to total dependency on support for daily life activities (2).…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the third phase of a larger project as a subanalysis. In the initial phases Dahlke et al, quantitative and qualitative data were collected and synthesised. Nursing staffs’ level of geriatric knowledge and perceptions about patient‐centred care, interprofessional practice and learning needs related to working with older people were examined.…”
Section: Primary Study and Aims Of The Third Phasementioning
confidence: 99%